Effect of Spirulina maxima on spatial memory in Rattus norvegicus var. albinus - Juan Luis Rodríguez Vega; Richard Fredy García Ishimine; Jorge Luis Campos Reyna; Davis Alberto Mejía Pinedo; Miryam Griselda Lora Loza; Wilmer Leoncio Calderón Mundaca (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: Memory is a physiological process that is activated by external stimuli.  It is necessary for behavior modification, adaptation to the environment, and differentiation in the animal model. This complex process that involves not only synaptic networks but other neurophysiological mechanisms, is usually stimulated by some nutraceuticals. Objective: To evaluate the effect of Spirulina maxima on spatial memory in Rattus norvegicus var. albinus. Material and Methods: An increasing stimulus design was developed.  Four similar groups of 5 rats were arranged and grouped into treatment I, II and III groups which were given Spirulina maxima orally at different concentrations; the control group did not received treatment. Spatial memory was assessed using the Morris water maze. Results: The rats presented an equal latency time to develop the acquisition and the retention phases; average times were recorded; the learning rates did not differ from each other at doses of 200 and 400 mg / kg; at the highest concentration dose of 800 mg / kg, there was a slight decrease in the latency time during the acquisition phase. There was a slight difference according to the ANOVA test. Conclusions. There was an effect of Spirulina maxima on the spatial memory of the experimental subject, which was evident in the duration of the motor behavior in the Morris water maze through learning rates which presented a favorable modification.